Harnessing the Harmonious Sounds of Naija Music as Tool for Ethnic Integration in Nigeria - Adewumi, Adeyinka Patrick; Adejumo, David Olushola (Kashere Journal of Politics and International Relations, 2024)
Nigeria, a nation of cultural diversity with several ethnic groups, has contended with challenges related to ethnic tensions and management strategies for national unity. In the continual search for measures of fostering national integration, this study looks at a different perspective on the role of contemporary Nigerian music, often called "Naija music," as a tool for fostering ethnic integration in the country. Relying on secondary sources such as articles, journals, texts, blogs and music data from streaming platforms, through content analysis, it observes that Naija music, characterised by its universal appeal, transcends geographical, linguistic, and cultural boundaries, making it a unifying force that brings Nigerians from various ethnic backgrounds together. This paper argues that the popularity of Naija music, characterised by artists with audiences across all states of the federation, can foster common bonds amongst the diverse entities within the country. This cross-cultural appreciation of Naija music demonstrates its potential as a unifying force in Nigeria. The findings of this research offer valuable insights into the use of music to foster national integration, enhance social cohesion, and promote unity among Nigerians, especially the youths who constitute a significant population.